Differing Effects of Younger and Older Human Plasma on C2C12 Myocytes in Vitro - Kalampouka, Ifigeneia; van Bekhoven, Angel; Elliott, Bradley T. (Frontiers in Physiology, 2018)
Ageing is associated with a general reduction of physiological function and a reduction of muscle mass and strength. Endocrine factors such as myostatin, activin A, growth and differentiation factor 11 (GDF-11) and their inhibitory peptides influence muscle mass in health and disease. We hypothesised that myocytes cultured in plasma from older and younger individuals would show an ageing effect, with reduced proliferation and differentiation in older environments. C2C12 myoblasts were grown as standard and stimulated with media conditioned with 5 % plasma from healthy male participants that were either younger (n = 6, 18 – 35 years of age) or older (n = 6, > 57 years of age). Concentration of plasma myostatin (total and free), follistatin-like binding protein (FLRG), GDF-11 and activin A were quantified by ELISA. Both FLRG and activin A were elevated in older individuals (109.6% and 35.1% increase, respectively), whilst myostatin (free and total) and GDF-11 were not. Results indicated that plasma activin A and FLRG were increased in older vs younger participants, GDF11 and myostatin did not differ. Myoblasts in vitro showed no difference in proliferation rate between ages, however scratch closure was greater in younger vs older plasma stimulated myoblasts (78.2% vs 87.2% of baseline scratch diameter, respectively). Myotube diameters were larger in cells stimulated with younger plasma than with older at 24 and 48 hours, but not at 2 hours. A significant negative correlation was noted between in vivo plasma FLRG concentration and in vitro myotube diameter 48 hours following plasma stimulation (r2 = 0.392, p = 0.030). Here we show that myoblasts and myotubes cultured in media conditioned with plasma from younger or older individuals show an ageing effect, and further this effect moderately correlates with circulating FLRG concentration in vivo. The effect of ageing on muscle function may not be innate to the tissue, but involve a general cellular environment change. Further work is needed to examine the effect of increased FLRG concentration on muscle function in ageing populations.